Mechanisms and influential factors of rock bursts in tunneling roadways of extra-thick coal seams - Yujie PENG; Qiang WANG; Anye CAO; Chengchun XUE; Guowei LYU; Qi HAO; Yaoqi LIU; Xianxi BAI; Dong LI (Meitian dizhi yu kantan)
ObjectiveRock bursts occur frequently in tunneling roadways of extra-thick coal seams, significantly constraining safe coal mining. Investigating their mechanisms and influential factors is crucial to preventing and controlling such disasters in tunneling roadways of extra-thick coal seams. MethodsFocusing on the tunneling roadway of mining face 250107-1 for an extra-thick coal seam within a coal mine in Gansu Province, this study established the discriminant indices for rock burst-induced roadway instability. By simulating the energy distribution patterns of surrounding rocks in the tunneling roadway using the FLAC3D software, this study revealed the zonal energy characteristics of the surrounding rocks and the mechanisms behind rock bursts in the tunneling roadway. Accordingly, this study analyzed the damage degrees of surrounding rocks of the tunneling roadway and the potential rock burst risk under different factors. Results and Conclusions The results indicate that the surrounding rocks of the tunneling roadway can be classified into areas according to elastic strain energy: energy accumulation, release, and buffer zones. The elastic strain energy accumulation zone serves as the principal source of the rock burst risk in the tunneling roadway, while the plastic dissipation energy accumulation zone is the primary damage zone of the surrounding rocks. The unloading and tunneling-induced disturbance increased both the elastic energy accumulation of deep surrounding rocks and the damage degree of shallow surrounding rocks. Then, a large quantity of the elastic energy accumulated in the deep rock masses was released, leading to the instantaneous displacement of the shallow damaged surrounding rocks. This induced rock bursts. The potential rock burst risk on both sides of the roadway increased with horizontal tectonic stress. In contrast, potential rock burst risk in coals on the top and bottom of the roadway increased and then decreased with an increase in the mining disturbance stress. Dynamic loading disturbance produced significant impacts on the damage degree of the surrounding rocks, and the potential rock burst risk gradually shifted to both sides of the roadway. Based on these results, this study proposed a synergistic rock burst prevention and control philosophy consisting of pressure relief, load reduction, and reinforcement for the tunneling roadways of extra-thick coal seams, effectively reducing the rock burst risk during roadway tunneling. This study provides a reference for the prevention and control of rock bursts in tunneling roadways of extra-thick coal seams.